Split‐Aperture Xolography – Linear Volumetric Photoactivation with Short Axial Dimension and Low out of Focus Excitation - Martin Regehly; Stefan Hecht (Advanced Science)
Abstract Spatially confined photo‐excitation with the lowest possible activation of the remaining volume is of central importance for high‐resolution high‐density optical data storage, fluorescence microscopy, 3D‐lithography, and 3D‐printing. Two‐photon absorption (2PA) enables such applications yet leads to slow processing speed due to the underlying non‐linear absorption process. Here, Split‐Aperture Xolography (SAX), is introduced which uses stepwise excitation of dual‐color responsive molecules to initiate a linear volumetric photo‐reaction process that is up to several orders of magnitude more efficient than 2PA. The capabilities of SAX are investigated in a scenario study for focusing systems with high numerical aperture (NA) using a Python implementation of vectorial diffraction theory. The intersecting half‐cones generated by the split illuminated entrance aperture of the objective reduce the axial focal spot size of the activation distribution by up to a factor of two compared to 2PA targeting the same electronic transition. A steep average decline of the activation probability with the fifth power away from focus is found for a wide range of directions. This is significantly better in comparison to 2PA and prevents that undesired out‐of‐focus excitation events sum‐up with subsequent irradiations. This approach is expected to be advantageous for volumetric methods at the nanoscale.